Canva-assisted project-based learning for collaborative competence and learning outcomes in civic education - Eva Selawati; Maria Montessori; Fatmariza Fatmariza; Junaidi Indrawadi (Global Econedu, 2026)
This study aimed to examine the effects of Project-Based Learning (PjBL) assisted by Canva on students' collaborative competence and learning outcomes in Civic Education. A quantitative approach employing a quasi-experimental nonequivalent control group pretest-posttest design was used. The participants consisted of 52 Grade X students at Muhammadiyah Private Vocational High School Batam, Indonesia, divided into an experimental group (n = 26) and a control group (n = 26). Data were collected through a collaborative competence observation sheet and a 25-item multiple-choice test. The findings revealed that the experimental group achieved significantly higher improvements in collaborative competence and learning outcomes than the control group (p < .001). The MANOVA results also demonstrated a significant simultaneous effect with a large effect size. Therefore, Canva-assisted PjBL is an effective instructional approach for improving collaborative competence and academic achievement in Civic Education